Pengembangan Media Pembelajaran Interaktif QRCode Berbasis Microsite Terhadap Kemampuan Memirsa Siswa Sekolah Dasar - Iis Siti Salamah Azzahra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The development of Information Technology, Industrial Revolution 4.0, and the impact of the Covid-19 Pandemic have changed students' behavior and learning styles, making them more accustomed to using technological devices. However, their interaction with the physical environment is reduced, hindering their ability to predict and observe. Therefore, media is needed that encourages students' viewing abilities while maintaining interaction with the objects being studied. This research aims to provide an overview of an alternative microsite-based QRcode interactive digital learning media designed with procedures for its application in the language learning process, especially in audience language skills. The research method used in this paper is literature study and also uses quantitative descriptive methods. The research results show that currently an alternative media is needed to help improve language skills, especially viewers. In response to this need, this paper was written to provide an overview of the design of an interactive application to help increase viewing of elementary school students using QRcode and microsites. With this interactive media, it is hoped that students will become more interested and improve their viewing abilities.